STRUCTURAL APPRAISAL: A CLASSICAL WAY FOR LEARNING - Kelly, Joseph Michael (ARCC Conference Repository, 2019)
Structural Analysis is an important subject in the Architecture curriculum at Temple University. Structural appraisal projects help a student understand architectural and structural integration, construction and technology, and address practitioners concerns for preparing students for practice. Projects incorporated in the Structural Analysis course typically focus on the documentation of historic structures. Students survey neglected and/or abandoned historic buildings that are in danger of collapse or demolition. The students are encouraged to appreciate the beauty in abandoned structures rather than view them as eyesores. They are required to integrate sustainable design and building conservation approaches in their solutions. On specific projects, they are required to 1) visually inspect the building and note damage, deficiencies and overall condition; 2) perform analysis of the existing structural system; 3) identify necessary repairs; 4) perform analysis of the building for varying stages of conservation, including associated cost estimates; and 5) determine a new use for the building. The students are encouraged to follow both the intuitive and mathematical paths in their analysis. Example projects include the historic Baptist Temple (from which Temple University is named), farmhouses, greenhouses, warehouses, barns and bridges. The goal of the projects is to illustrate the significant impact of the integration of structure and architecture and educating students about the significant contribution they can make to protect historic structures.